2018
DOI: 10.1021/acs.jpcc.8b02080
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of LiPF6 in Carbonate-Based Electrolytes for Lithium-Ion Batteries and in Aqueous Media

Abstract: The conducting salt in lithium-ion batteries, LiPF6, can react with water contaminations in the battery electrolyte, releasing HF and further potentially harmful species, which decrease the battery performance and can become a health hazard in the case of a leakage. In order to quantify the hydrolysis products of LiPF6 in a water-contaminated battery electrolyte (1 mol L–1 LiPF6 in EC/DEC) and in aqueous solution, ion chromatography (IC), coulometric Karl Fischer titration (cKFT), and acid–base titration were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 29 publications
2
119
0
Order By: Relevance
“…Stich et al reported that the reaction between LiPF 6 and water yields three molar equivalents of HF, as determined using ion chromatography. [26] According to the literature, the HF content in the electrolytes were calculated to be 8.2 and 99.7 mmol dm À 3 , respectively. The water content of the electrolyte with 100 ppm added water was similar to the control sample after approximately 10 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stich et al reported that the reaction between LiPF 6 and water yields three molar equivalents of HF, as determined using ion chromatography. [26] According to the literature, the HF content in the electrolytes were calculated to be 8.2 and 99.7 mmol dm À 3 , respectively. The water content of the electrolyte with 100 ppm added water was similar to the control sample after approximately 10 days.…”
Section: Resultsmentioning
confidence: 99%
“…The film repair process is kinetically faster in a fluorinated electrolyte than in an unfluorinated electrolyte. [45] HF and fluorophosphoric acid were formed in the electrolyte with 100 ppm of water, [26] thus the rapid formation of the surface film containing these compounds likely enabled the deposition of columnar metallic lithium. The morphology of the deposited lithium was heavily dependent on the type of electrolyte, the concentration of electrolyte salt, and the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded a high influence of moisture in the system affecting the decomposition behavior of the electrolyte as quantities of decomposition products increased immensely depending on the amount of added water. In 2018, Stich and coworkers compared the hydrolysis of LiPF6 in carbonate-based electrolytes for LIBs and in aqueous media [179]. They proposed the reaction of POF3, an intermediate of the decomposition route of the conducting salt, to be fast in order to align with the results of their study.…”
Section: Ion Chromatographymentioning
confidence: 99%
“…In addition, IC was used for the analysis of Li + , CO3 2− , SO4 − and F − . The use of pyrolysis or TPD GC-MS, respectively, was In 2018, Stich and coworkers compared the hydrolysis of LiPF 6 in carbonate-based electrolytes for LIBs and in aqueous media [179]. They proposed the reaction of POF 3 , an intermediate of the decomposition route of the conducting salt, to be fast in order to align with the results of their study.…”
Section: Pyrolysis-gc-msmentioning
confidence: 99%
“…LiPF 6 is unstable at temperatures above 60 1C and it readily reacts with trace amounts of water due to its high hydrophilicity, leading to several decomposition reactions. [27][28][29][30] Kock et al 31 reported that the Raman spectrum for pristine, anhydrous alkali metal-PF 6 salts presents four intense bands at 475, 560, 571 and 745 cm À1 assigned to the E g , T 1U , T 2g and A 1g vibrations of PF 6 À anion, respectively. Fig.…”
Section: Kerr Gated Raman Studies Of Lithium Hexafluorophosphate Saltmentioning
confidence: 99%